A Review of Noninfectious Diseases Masquerading as Acute Mastoiditis. (7th December 2021) - Wong, Kevin; Arrighi‐Allisan, Annie E.; Fan, Caleb J.; Wanna, George B.; Cosetti, Maura K.; Perez, Enrique R.
Abstract : Objective: Acute mastoiditis is commonly attributed to infection. Rarely do clinicians encounter cases that do not respond to traditional antibiotics or surgical management. The goal of this study was to systematically review the literature to characterize diseases masquerading as acute infectious mastoiditis. Data Sources: PubMed, Embase, and Scopus. Review Methods: A systematic review was performed to identify all publications that reported on diseases with presentations mimicking acute mastoiditis, defined as postauricular redness, swelling, and tenderness. We included clinical prospective studies, retrospective studies, and case series/reports. Exclusion criteria included non‐English articles, letters/commentaries, abstracts, and review articles. Results: Out of 3339 results, 35 studies met final inclusion criteria. In children, 11 diseases were reported to mimic mastoiditis, including solid tumors, hematologic diseases, and autoimmune/inflammatory diseases. The most common disease in children was Langerhans cell histiocytosis, followed by rhabdomyosarcoma and acute myelogenous leukemia. In adults, 8 additional diseases were reported. The most common disease in adults was squamous cell carcinoma, followed by nasopharyngeal carcinoma and Langerhans cell histiocytosis. Presenting symptoms are reviewed, as well as characteristic radiographic, laboratory, and intraoperative features that may assist with diagnosis. A diagnostic algorithm for atypical cases of acute mastoiditis is proposed. Conclusion: A small but significant group of diseases in children and adults can mimic acute mastoiditis. In such cases, history and examination alone may be insufficient to reach a diagnosis, and further investigation may be necessary. Otolaryngologists should always be mindful of the possibility that noninfectious pathologies may present with a constellation of symptoms similar to mastoiditis.